Transient Epileptic Amnesia: A Treatable Cause of Spells Associated With Persistent Cognitive Symptoms - Ramanan, Vijay K; Morris, Kenneth A.; Graff-Radford, Jonathan; Jones, David T.; Burkholder, David B.; Britton, Jeffrey W.; Josephs, Keith A.; Boeve, Bradley F.; Savica, Rodolfo (Frontiers in Neurology, 2019)
Objective: To characterize the clinical, EEG, and neuroimaging profiles of transient epileptic amnesia (TEA). Methods: We performed a retrospective analysis of patients diagnosed with TEA at the Mayo Clinic Minnesota from January 1, 1998-September 21, 2017. Diagnostic criteria included the presence of recurrent episodes of transient amnesia with preservation of other cognitive functions and evidence for epilepsy (epileptiform abnormalities on EEG, clinical features of seizures, or symptomatic response to anti-seizure medications). Results: Nineteen patients were identified (14 men, 5 women) with median onset age 66 years and median time to diagnosis 2 years. Thirteen patients (68%) reported persistent cognitive/behavioral symptoms, including 4 (21%) for whom these were the chief presenting complaints. EEG revealed epileptiform abnormalities involving the frontal and/or temporal regions in 12/19 individuals (63%), including activation during sleep in all of these cases. In numerous cases, sleep and prolonged EEG evaluations identified abnormalities not previously seen on shorter or awake-state studies. Brain MRI revealed focal abnormalities in only 4/19 cases (21%). FDG-PET identified focal hypometabolism in 2/8 cases where it was performed, both involving the frontal and/or temporal regions. Anti-seizure therapy, most often with a single agent, resulted in improvement (reduction in spell frequency and/or subjective improvement in interictal cognitive/behavioral complaints) in all 17 cases with available follow-up. Conclusions: TEA is a treatable cause of amnestic spells in older adults. This syndrome is frequently associated with persistent interictal cognitive/behavioral symptoms and thus can be mistaken for common mimics. In the appropriate clinical context, our findings support the use of early prolonged EEG with emphasis on sleep monitoring as a key diagnostic tool. FDG-PET may also complement MRI in distinguishing TEA from neurodegenerative disease when suspected.